2002
DOI: 10.1103/physrevd.66.105013
|View full text |Cite
|
Sign up to set email alerts
|

Vortices in theories with flat directions

Abstract: In theories with flat directions containing vortices, such as supersymmetric QED, there is a vacuum selection effect in the allowed asymptotic configurations. We explain the role played by gauge fields in this effect and give a simple criterion for determining what vacua will be chosen, namely those that minimise the vector mass. We then consider the effect of vacuum selection on stable (BPS) non-topological vortices in a simple Abelian model with N = 2 supersymmetry which occurs as a low energy limit of Calab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…In ref. [15,16] vortices in N= 1 QED were considered and it was concluded that in generic point on the Higgs branch the string is unstable. The only vacuum which support string solutions is the base point of the Higgs branch <q >= 0.…”
Section: String In a Generic Vacuummentioning
confidence: 99%
See 3 more Smart Citations
“…In ref. [15,16] vortices in N= 1 QED were considered and it was concluded that in generic point on the Higgs branch the string is unstable. The only vacuum which support string solutions is the base point of the Higgs branch <q >= 0.…”
Section: String In a Generic Vacuummentioning
confidence: 99%
“…The only vacuum which support string solutions is the base point of the Higgs branch <q >= 0. The so called "vacuum selection rule" was put forward in [15,16] to ensure this property. We would like to stress that our results here and in ref.…”
Section: String In a Generic Vacuummentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of a flat direction on BPS vortices of the ANO type was discussed in refs. [41,42]. Now we show that the BPS equations can be obtained by imposing SUSY transformation of the fermions to be zero.…”
Section: Jhep09(2017)046mentioning
confidence: 99%